(untitled) (Research, Society and Development, 2022)
Objective: To observe possible association between the occurrence of infectious diseases during the first two years of life and the occurrence of asthma symptoms in six-year-old children. Methods: Cross-sectional study involving 956 six-year-old schoolchildren. Asthma symptoms were assessed through International Study of Asthma and Allergies in Childhood questionnaires. Socio-demographic data, mother-reported infectious diseases during the child’s first two years of life, family history of asthma and breastfeeding were included. Multivariate analysis was performed with all significant variables and those with a p-value <0.20 using Poisson Regression with a robust estimator. Results: The reported wheezing or whistling in the chest in the past 12 months prevalence was 18.7%. There was found a 9% higher prevalence of asthma at six years of age in children who had had respiratory infections in the first two years of life. Children with a family history of asthma had a 7% higher and independent prevalence of asthma at six years of age and those breastfed presented 6% lower independent prevalence of asthma at six years of age. Conclusions: Higher prevalence of asthma reports at six years of age was found in children whose mothers reported infectious respiratory diseases during the first two years and with family history of asthma. Lower prevalence was observed in breastfed children in the first two years of life.